2014
DOI: 10.1037/a0037451
|View full text |Cite
|
Sign up to set email alerts
|

Affect dynamics across the lifespan: With age, heart rate reacts less strongly, but recovers more slowly from unpleasant emotional situations.

Abstract: We propose that a comprehensive understanding of age differences in affective responses to emotional situations requires the distinction of 2 components of affect dynamics: reactivity, the deviation from a person's baseline, and recovery, the return to this baseline. The present study demonstrates the utility of this approach with a focus on age differences in responses of negative affect and heart rate to an unpleasant emotional situation in 92 participants aged 14 to 83. The emotional situation was elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 64 publications
4
33
1
Order By: Relevance
“…Our goal was to test hypotheses extended to SAVI, which uses a generalized conception of negative affect. However, our follow-up tests with separate NA items are partially in line with Wrzus and colleagues’ (2014, 2015) studies using high and low activation NA items. For example, we found that depressed/blue showed reactivity about half the magnitude of the other NA items and a relatively flat recovery profile.…”
Section: Discussionsupporting
confidence: 86%
“…Our goal was to test hypotheses extended to SAVI, which uses a generalized conception of negative affect. However, our follow-up tests with separate NA items are partially in line with Wrzus and colleagues’ (2014, 2015) studies using high and low activation NA items. For example, we found that depressed/blue showed reactivity about half the magnitude of the other NA items and a relatively flat recovery profile.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, as people grow older, their emotion regulation performance tends to improve (Doerwald et al, 2016; see also Blanchard-Fields, 2007), and they are less likely to externalize and lash out at interpersonal conflict (Diehl, Coyle, & Labouvie-Vief, 1996;Rook & Charles, 2017). At the same time, people experience more distress as they age when their social needs are not met (Ong, Rothstein, & Uchino, 2012), and their physiological recovery from stress also becomes impaired as biological aging sets in (Wrzus, Müller, Wagner, Lindenberger, & Riediger, 2014). Notably, these respective strengths and vulnerabilities have been documented even among people in their 30s relative to those in their 20s (Diehl et al, 1996;Wrzus et al, 2014).…”
Section: Integrating the Strengths And Vulnerabilities Of Agingmentioning
confidence: 99%
“…At the same time, people experience more distress as they age when their social needs are not met (Ong, Rothstein, & Uchino, 2012), and their physiological recovery from stress also becomes impaired as biological aging sets in (Wrzus, Müller, Wagner, Lindenberger, & Riediger, 2014). Notably, these respective strengths and vulnerabilities have been documented even among people in their 30s relative to those in their 20s (Diehl et al, 1996;Wrzus et al, 2014). Altogether, these strengths and vulnerabilities both influence threat, although at different stages.…”
Section: Integrating the Strengths And Vulnerabilities Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…less contractile strength, lower stroke volume) may impair responsiveness to and recovery from physiologically arousing emotional states. For example, although age differences are not observed in subjective distress, heart rate increases are smaller and recovery takes longer in older compared to younger adults [54]. …”
Section: Selectivity As a Function Of Socioemotional Goalsmentioning
confidence: 99%